PENANGANAN IKAN HASIL TANGKAPAN DIATAS KAPAL PENAMPUNG (COLLECTING) DI PPS NIZAM ZACHMAN JAKARTA - siahaan, irandha C. M; suhono, Lego; Lewo, Roy Linus Gawi (Universitas Mataram, 2025)
Fish handling is a series of treatments that are carried out on fish without changing the nature of the fish itself. Good handling will produce fish quality with good quality. A container ship is one of the types of ships that focus on carrying out fish shelter and handling activities. This study aims to find out the process of handling fish on a container ship, and find out the number of fish handled. This research was carried out on board the KM flotation vessel. Fortuna VI which is anchored at PPS Nizam Zaman North Jakarta. The method used in this study is descriptive by directly following the process of handling fish on the ship. From the results of observations during the study, it is known that fish handling on a container ship consists of the stages of preparation, handling, fish preparation, freezing, and unloading on land. Meanwhile, the number and type of fish handled were skipjack fish (59%), yellowfin tuna (36%), and Layang 4%).